Trajetos formativos e significações imaginárias: as narrativas de professoras da EBTT - Porto, Eliane Quincozes (2018)
This dissertation presents the research carried out with teachers of Basic Technical and Technological Education and had the purpose to understand how their formative paths and their teaching knowledge were constituted in a pedagogical performance in courses historically considered as masculine. In this sense, I sought to know the formative journey and the teaching knowledge from the perspective of Gender Studies, investigating the possible implications of being a woman in her professional construction, mapping the meanings of teaching they have built, and also trying to understand, along with them, the influence of their gender in the rise or institutional collaboration. For that, my methodological choice was the qualitative research through oral narratives of life. For the production of data, individual interviews were conducted, semi-structured guided with the teachers, and their teaching practice was problematized, with the intention of encouraging the interlacing of the narrated data with their planning and implementation. Data analysis was organized from the assumptions of the Thematic Categorical Content Analysis. I conducted interviews with teachers from different courses of a Federal Institute of Education, Science and Technology in order to seek important meanings in the formative paths of each one, confirming the approximation between personality and professionalism, being that in describing themselves teachers also do while women. As for the crossings of their gender in teaching in spaces considered as "for men", they are pointed out as meanings instituted in the socio-historical context. With regard to the possible influences of their gender for professional ascension and collaboration, the presence of issues related to power relations appear imbricated in these spaces of formation and work.